The Concircular Curvature Tensor Of The Locally Conformal Kahler Manifold - Ali Abdalmajed. Shihab; Dheyaa Nathim Ahmed (Tikrit Journal of Pure Science, 2019)
In this research, we are calculated components conharmonic curvature tensor in some aspects Hermeation manifolding in particular of the Locally Conformal Kahler manifold. And we prove that this tensor possesses the classical symmetry properties of the Riemannian curvature. They also, establish relationships between the components of the tensor in this manifold.